Marking and Memory: An Embroidered Sheet in the Collection of the Victoria and Albert Museum. (3rd May 2016) - Brodie, Antonia
Abstract: In 2006 the Furniture Textiles and Fashion Department of the V&A received a package. Inside the parcel were a large linen bed sheet and a photograph of a woman in nineteenth-century dress with an accompanying note, but no indication of the donor's name or address. The sheet was late sixteenth century, comprising two widths of hand-woven linen joined by a bobbin lace insertion. Finished at the corners and at the end of the insertion with tassels, it was embroidered with six sets of initials, four of which bore dates ranging from 1786 to 1900. According to the note that accompanied the anonymous donation, these initials referred to the individuals for whose laying-out after death this sheet was used. Research has shown that the initials in fact record marriages, significantly altering the meaning of the object and the commemoration it appears to represent, associated not just with death but also, perhaps instead, with other noteworthy events in its owners' lives. The sheet presents a unique opportunity to explore the material goods of several generations of one family and to build a picture of the role that objects can play in marking and celebrating emotional experience.